Rancang Bangun Sistem Informasi Manajemen Pada PT Mitra Jaya Keramik - Jessica Yulistia; Yulistia Yulistia (Publikasi Indonesia, 2022)
Running a business requires science and technology. Businesses need knowledge to know what will be developed and will be run and technology to manage and produce data that is precise, accurate and efficient. the application of information technology in business is to use a computer-based information system for both staff and managers. One of the computer-based information systems that can assist managers in obtaining information in their respective units is the Management Information System. The method used in the development of the system used to analyze and design this system is the Iteration methodology (Iterative model). Management information systems can be used by managers in which there is data relating to sales, purchases, inventories and others where the data can produce information that will be useful for managers to know the results of the company's development. This system is intended to make it easier for managers to check purchasing information, sales information, inventory information, inventory information and information to be reported. The results of this system, so that managers can see sales results in detail because they can find out the total sales per day, month and year. The accounts receivable section can view detailed and detailed information on receivables that have been paid off and those that are still due. The purchasing department can see information about debts that have been paid and those that are still due.